Totalitarian speech - Głowiński, Michał 1934-2023 (Studien zur kulturellen und literarischen Kommunismusforschung, 2014)
Totalitarian Speech brings together a range of texts on totalitarian manipulations of language. The author analyzes various phenomena, from the hateful rhetoric of Nazi Germany to the obfuscating newspeak of communist Poland, finding certain common characteristics. Above all, totalitarian speech in its diverse manifestations imposes an all-embracing worldview and an associated set of dichotomous divisions from an omniscient and authoritative perspective. This volume collects the work of over three decades, including essays written during the communist era and more recent pieces assessing the legacy of totalitarian ways of thinking in contemporary Poland